Effect of Childbearing on Female Labour Supply: An Empirical Study in Taiwan. Issue Volume 16:Issues 1(2017) (2nd January 2017) - Lin, Hung-Han
ABSTRACT: In society, women generally play the roles of mothers and employees, and those roles are partly substitute to each other; therefore, the contributions of women to the labour market should be considered. This paper applied the widely observed parental preference for children's sex as an instrumental variable for the number of children in Taiwan and examined the causal effect of childbearing on female labour supply. Ordinary least square estimates revealed that childbearing is associated with reduced female labour supply. However, after using the sex of first and second children as instruments to account for the endogeneity of the number of children, two-stage least square estimates revealed no correlation between the number of children and female labour supply.